Contradições entre capital e trabalho: concepções de educação tecnológica na reforma do ensino médio e técnico - Silveira, Zuleide Simas da (2007)
This dissertation has the general objective of analyzing the conceptions of technologic education dating from the educational policy during Fernando Henrique Cardoso s government, mediated by Decree n. 2.208/97. The text is structured in three chapters. The first one analyzes political economy within world context, in general, and in Brazil in particular, pointing out the effects of the economic disturbances in work market. In the second one, it is analyzed the relationship between work and education, also the relationship among work, sciences and technology so as to understand the role of science, of know-how and technology in human culture global structure and how this relationship has been confiscated by capital. Then, historical rebuilding of professional education in Brazil is pointed out, having as focus of analysis federal net technical schools. Lastly, it is revealed the movement of the pedagogical thought facing professional education and its done in everyday academic CEFET/RJ. The research results show that the reform brings forward a productivist and dual vision of education, coming close to the conception of human capital , inducing institutions pertaining to the Technologic Education Federal Net to adapt to work market.